13Z+17=0

Simple and best practice solution for 13Z+17=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13Z+17=0 equation:


Simplifying
13Z + 17 = 0

Reorder the terms:
17 + 13Z = 0

Solving
17 + 13Z = 0

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + 13Z = 0 + -17

Combine like terms: 17 + -17 = 0
0 + 13Z = 0 + -17
13Z = 0 + -17

Combine like terms: 0 + -17 = -17
13Z = -17

Divide each side by '13'.
Z = -1.307692308

Simplifying
Z = -1.307692308

See similar equations:

| -6*8-8y=48 | | 4x^2+12x-5= | | 111-2x=6x | | 4/4.333 | | 4/4.333 | | 4*6+10y=40 | | 27x-11-15x=3(4x-5)+4 | | p-88-18=72/5(h-7) | | 9(m-3)-7m=2(m-13)-1 | | 16x^3-36=0 | | 6*22/7 | | -88-18=72/5(h-7) | | 12+2x+10=3x+18-5x | | 5b+7=b-2 | | 256-9x=20 | | (v^15y^-6)^7/3 | | 4(-4)+10y=40 | | Y-18-36Y=3 | | f/6-1.2=-30 | | 9x-12=19x | | 1/2x+9=36 | | 3a-8=4a+3 | | (-3)(-3)-5=8-2x | | (v^15y^-6)7/3 | | 6x-2(x-1)=8x+15-3x | | 7x+37=32 | | Y=x^2+3x-22 | | 3(-12z-5)+10=12(-3z+5)-61 | | p-88=72/5(88-7) | | 7.5+0.5x+3/4x | | 7p+22p+3=0 | | p-17/1=72/5(-7) |

Equations solver categories